2008
DOI: 10.1136/jcp.2007.054296
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT-guided biopsy in the diagnosis of septic discitis

Abstract: Septic discitis is a serious condition with a wide variety of infective causes. CT-guided biopsy is a useful tool when the diagnosis of infectious spinal infection is considered in terms of commencing and targeting therapy, and it is a safe and well-tolerated procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 11 publications
2
61
0
2
Order By: Relevance
“…Other authors continue to advocate early biopsy when blood culture is negative [11][12][13][14][15]. Disc space biopsy is associated with minimal morbidity and, for cases in which microbial identification is successful, aids in the selection of appropriate antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors continue to advocate early biopsy when blood culture is negative [11][12][13][14][15]. Disc space biopsy is associated with minimal morbidity and, for cases in which microbial identification is successful, aids in the selection of appropriate antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some experts recommend a second percutaneous biopsy if the first one is negative Fig. 4 Distribution of the microbiological findings after percutaneous disc biopsies or blood cultures [11][12][13][14][15]. Friedman [16] reported positive initial percutaneous biopsy cultures for 50% of 24 patients with spontaneous spondylodiscitis, a frequency that improved to 79% on repeat biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Culture from biopsy allows micro-organism identification in more than half of patients. Less invasive percutaneous biopsy is a safe procedure and can be taken either by guided CT-scan or by endoscopy [15]. Endoscopy also allows discectomy and drainage, and its performance for bacterial recovery is better than CT-guided spinal biopsy [68].…”
Section: Biopsymentioning
confidence: 99%
“…Since biopsy after antibiotic treatment may end in a negative culture [13,15], antibiotic suppression prior to the biopsy should be the rule. However this is a controverted issue as nearly 40% of spondylodiscitis without prior antibiotic treatment may present a negative culture [20].…”
Section: Biopsymentioning
confidence: 99%
“…18 Enoch et al reviewed 98 CT-guided procedures in 103 patients; only 9 of 25 samples (36%) were positive for cultures. 11 In a 2013 retrospective study of image-guided biopsy, Kim et al reported a 97.1% overall success rate. They later claimed a 78.8% success rate (134/170) in the diagnosis of infection; however, this statistic is based on the diagnosis of infection by histology or clinical outcome.…”
mentioning
confidence: 99%